IMPACT OF GRANT PROJECTS IMPLEMENTATION IN ROMANIAN HIGHER EDUCATION INSTITUTIONS - Vlad S. PETCU; Ioan LALA POPA (Management Intercultural, 2016)

(untitled)
Romanian Higher Education Institutions were one of the main beneficiaries of European funding in the 2007-2013 funding excercise, especially in the Sectoral Operational Programme Human Resources Development. Analyzing the data provided by 21 public universities in Romania, we find that Universities have accessed in a significant proportion two types of projects: those dedicated to transition from school to active life and those dedicated to doctoral studies. Also, the proportion of the European funds attracted by HEIs is an overwhelming part of the allocation of reference (over 40% since 2011), and also a significant proportion of total revenues universities (~15.5 % for 2011-2014).